Factors affecting the effect of exploitation and exploration on performance: A meta-analysis - Diego Armando Marín-Idárraga; José Manuel Hurtado González; Carmen Cabello Medina (BRQ Business Research Quarterly, 2022)
From a contingency view, we aim to contribute to a better understanding of how exploitation and exploration influence performance. By conducting a meta-analysis, we aim to answer the following research question: How do substantive moderators (slack resources, organizational structure, inter-organizational relationships, competitive intensity, and environmental dynamism), extrinsic moderators (region, size, and sector) and methodological moderators (data sources and performance measurement) affect the impact of exploitation and exploration on performance? The results of the meta-analysis, including 328 correlations, 102 studies, and a sample of 41,298 cases, suggest that the influence of exploitation and exploration on performance depends on the presence of the moderating factors included in our analysis. Furthermore, some of these factors are relevant for explaining a better performance of exploitation versus exploration, while other moderators do not determine a different effect of exploitation and exploration on performance.
Keywords: M10; M19; O3; 650; Exploitation; exploration; meta-analysis; moderating factors; performance